On a moment theorem for complex Gaussian processes - Reed, I. (I.R.E. transactions on information theory, 1962)
A general theorem is provided for the moments of a complex Gaussian video process. This theorem is analogous to the well-known property of the multivariate normal distribution for real variables, which states that an n th order central product moment is zero if n is odd and is equal to a sum of products of covariances when n is even.